THE EFFECT OF SEEDLING THICKNESS AND NORMS OF MINERAL FERTILIZERS ON THE ACCUMULATION OF RHIZOME MASS AND DRY MASS OF BEETS - Xalikov Baxodir Meylikovich; Esirgapova Umida Xasanovna (Web of Journals Publishing, 2025)
validity period, and the following September and October the process will be slow. This article provides information on the influence of seedling thickness and ore fertilizer norms on the accumulation of rhizome mass and dry mass of beets.